Pelatihan Pembuatan Katalog Digital sebagai Media Promosi Produk UMKM Kota Kendari - Nurul Ittaqullah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of digital technology has transformed product marketing from conventional approaches to digital-based promotional strategies. Although many Micro, Small, and Medium Enterprises (MSMEs) have utilized social media as a promotional platform, the quality of their promotional content remains limited and often fails to present product information in an attractive and professional manner. This condition highlights the need to strengthen MSMEs' competencies in developing effective digital promotional media. This community service program aimed to improve the knowledge and practical skills of MSME owners in designing digital product catalogs as a promotional tool. The program was conducted in Kendari City using a participatory educational approach consisting of three stages: preparation, implementation, and evaluation. The implementation included presentations on the importance of digital promotion for MSMEs, demonstrations of digital catalog examples on Instagram, hands-on training in creating digital catalogs, participants' presentations, and program evaluation. The results indicated that participants gained a better understanding of digital promotion strategies, acquired practical skills in designing digital catalogs, and successfully produced attractive and informative promotional catalogs ready for publication on social media platforms. Overall, the program contributed to strengthening participants' digital competencies and supported the improvement of digital marketing practices among MSMEs.